Fatores que impactam em internação prolongada nos pacientes submetidos a cirurgias ortopédicas de membros inferiores no Hospital Universitário de Santa Maria - Dalla Lana, Daniela (2023)
Introduction: Orthopedic trauma is one of the most morbid conditions, often surgically treated, which compromises the individual's function, economic participation and social integration. Falls from heights constitute an important problem in the elderly and fractures, especially of the femur, which can lead to complications, including death. The main cause of lower limb fractures in young people are traffic accidents, with motorcycles being responsible for the highest number of cases. Prolonged hospitalization presents complications for the patient's quality of life, increasing the risk of morbidity and mortality, resulting in an increase in hospital costs. Objective: It is important to identify factors that impact prolonged hospitalization in patients undergoing lower limb orthopedic surgeries at the HUSM. Method: This is a cross-sectional, descriptive study. All patients/caregivers who agreed to participate in the research were interviewed to obtain data prior to hospitalization and trauma kinematics. Data on hospitalization were analyzed using the electronic medical record of the AGHU system, with a time frame from July/2021 to March/2022 and daily inclusion of patients. Results: Of the 182 patients evaluated, 25.3% had a length of stay within the average for Rio Grande do Sul (7 days). There was a higher prevalence of male patients (65.9%). Comorbidities and risk factor with statistical significance in patients with prolonged hospitalization were SAH (p<0.001), smoking (p=0.031), diabetes (p<0.001), dyslipidemia (p=0.013) and osteoporosis (p=0.004). Among the fractures, 45.1% femur fractures, 19.8% tibia fractures, 15.4% tibia and fibula fractures, 9.3% malleolar fracture (ankle). Motorcycle accidents had the highest percentage of patients (29.1%), followed by falls from heights (23.1%), falls from standing heights (18.7%), car accidents (10.4%), being run over (9 .8%), gunshot wounds (4.4%), stab wounds (1.6%) and blunt trauma (2.7%). Regarding canceled surgeries, 37 out of 182 surgeries were canceled at least once. Conclusion: For the most part, patients had a prolonged hospitalization time for several reasons, other than those inherent to their clinical condition. When we analyzed age, trauma mechanism, presence of femur fracture or comorbidities, none was significant in relation to the mean length of hospital stay. On the other hand, infection requiring the use of antibiotics and clinical complications in the pre- or postoperative period, exposed fractures and surgery cancellations had a significant impact on the number of days in hospital. It is essential to identify, at the time of admission, patients at risk of delay in discharge, who need complex discharge planning, monitoring situations considered at risk. Continuous knowledge of surveillance indicators is necessary to reduce pre/postoperative infections, as well as indicators of people and material/surgical room management to avoid unnecessary suspension of surgeries due to lack of planning or physical or human material.